1995
DOI: 10.1080/17450399509381808
|View full text |Cite
|
Sign up to set email alerts
|

Methodical investigations on the metabolism oriented determination of methionine requirement of broiler chickens

Abstract: In a chicken experiment was investigated, whether the kind of applied isotope and labelling site influence the results of the metabolism oriented estimation of the methionine requirement. Furthermore it was studied, if this method can give additional informations to weight gain and N-retention data concerning methionine requirement. 48 male broiler chickens received synthetic diets with a complete amino acid mixture from day 7 posthatching. The methionine content of the 8 experimental diets varied from 2.25 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
2
3
0
Order By: Relevance
“…The results are well in confirmation with those reported by Ozturkan et al 13 that supplementation of choline, methionine and lysine to broilers improved performance in terms of feed efficiency and livability. Similar results were also given by Simone et al 14 and Ohta and Ishibashi 10 that supplementing herbal or synthetic sources of essential amino acids improved feed to body weight gain ratio in broilers.…”
Section: Growth Parameterssupporting
confidence: 86%
“…The results are well in confirmation with those reported by Ozturkan et al 13 that supplementation of choline, methionine and lysine to broilers improved performance in terms of feed efficiency and livability. Similar results were also given by Simone et al 14 and Ohta and Ishibashi 10 that supplementing herbal or synthetic sources of essential amino acids improved feed to body weight gain ratio in broilers.…”
Section: Growth Parameterssupporting
confidence: 86%
“…Similar study by Holsheimer and Veerkamp (1992) reported that the broiler ratio with equal CP content and high-Lys gave significantly more gain (P < 0.05) than the normal-lysine diets. Simon et al (1995) concluded that under reducing dietary protein by 10% could have no inappropriate effect on broiler performance; while in addition, increase in methionine level by 20% could improve broiler performance, similar result was also observed by Torki (2007). Considerable research has been found published in different research journals on this aspect.…”
Section: Discussionsupporting
confidence: 72%
“…Some researchers have shown that reduced crude protein-amino acid supplemented diets support good growth and feed consumption of broilers (Aletor et al, 2000). Addition of methionine over and above the recommended requirement of broilers improves their performance in terms of body weight gain and food conversion efficiency (Simon et al, 1995). Therefore, the objective of this study was to evaluate the influence of low protein broiler diet supplemented with or without amino acids on the production of broiler.…”
Section: Introductionmentioning
confidence: 99%
“…In this previous study, neither the N excretion nor the health characteristics of the animals were taken into account. Further studies, carried out in the 1990s confirmed that performance (BWG and FCR) improved with a Met supply above the recommendation [64,65,66]. For this reason, Aviagen ® publishes Nutrition Specifications for Ross ® broilers [40], referring to nowadays animal performance and recommending the following regarding Met: starter 5.6 g/kg diet; grower: 5.1 g/kg diet; finisher: 4.7 g/kg diet.…”
Section: Discussionmentioning
confidence: 94%